The Influence of the Job Market and Technology on the Gig Economy on the Bugis Muslim Community - Adil, Adil; Munawarah, Munawarah; Jumriani, Jumriani (Riviera Publishing, 2025)
Globalization caused changes in the job market and gave rise to a new segment in the job market called the Gig Economy. Gig Economy is a general term used to describe a job market dominated by freelancers or temporary jobs centered on the internet. This study uses a quantitative research method. This research data uses primary and secondary data with the distribution of a questionnaire of 100 millennial generation respondents in the city of Wattampone. The sampling technique uses the Random Sampling technique. The results of this study show that (1) The job market has a significant effect on the Gig economy. (2) Technology has a significant effect on the gig economy. (3) The job market and technology have a simultaneous effect on the Gig Economy.